Ethnobotanical study on using bamboo for kites making in Sumedang District, West Java, Indonesia - MUHAMMAD IHSAN; BUDI IRAWAN; BUDIAWATI SUPANGKAT ISKANDAR; JOHAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ihsan M, Irawan B, Iskandar BS, Iskandar J. 2023. Ethnobotanical study on using bamboo for kites making in Sumedang District, West Java, Indonesia. Biodiversitas 24: 2393-2401. Bamboo has diverse socio-economic, cultural, and ecological roles in rural areas. Residentsin Cijambu Village, Tajungsari District, Sumedang Regency, West Java, usually use bamboo for kite crafts based on local or Traditional Ecological Knowledge (TEK). However, currently, the craft activities of the residents of Cijambu Village in making kites tend to decline. This is due to the reduced kite demand, and the younger generation is less interested in kite-making crafts. As a result, it is difficult for the kite-making industry in Cijambu Village to provide jobs and creates an opportunityfor the villagers to maintain its sustainability. In addition, the decline in the kite-making industry could cause the gradual erosion and subsequent loss of the TEK. Therefore, this study aims to elucidate the TEK of Cijambu Village on bamboo species and landraces, the utilization of bamboo for the kite-making industry, and its benefits for rural communities. The method used in this study was qualitative with an ethnobotanical approach; there are 12 informants comprising seven men and five women between the ages of 35 and 70 years involved in this study. The resultof the study showed thata total of 5 landraces and species of bamboo, i.e.: awi tali (Gigantochloa apus (Schult.f.) Kurz), awi bitung (Dendrocalamus asper (Schult.f.) Backerex K. Heyne), awi surat (Gigantochloa verticillata (Willd.) Munro), awi gombong héjo (Gigantochloa verticillata (Willd.) Munro), awi temen (Gigantochloa atter (Hassk.) Kurz),and awi haur konéng (Bambusa vulgaris Schrad. ex J.C.Wendl. var. Striata (Lodd.ex Lindl.) Gamble) in Cijambu Village. The G. apus have predominantly been used for making kites, creating many job opportunities for men and women, and diversifying household income. However, the future sustainability of the kite industry in Cijambu Village tends to be very challenging because the demand for kites is declining occasionally. At the same time, the younger generation is less interested in kites making, and the TEK gradually erodes withinthe younger generation. Thus, it was revealed that the use of bamboo for the kite craft industry had formed biocultural systems, as well as changes in the culture and linguistics of villagers, which can affect the management and conservation of bamboo in rural areas.